Awarded cooperation agreement, procedural paternalism and "chameleon judges": simplification and efficiency of procedure in the fight against corruption - Paulo Roberto Fonseca Barbosa (Revista Brasileira de Direito Processual Penal)
Detecting a kind of procedural paternalism in the performance of judges, it is sought to demonstrate that the double judicial analysis of the awarded cooperation agreement, as provided for by Law 12.850/2013, is a point of destabilization of the Brazilian negotiated criminal justice system, contributing negatively to a series of procedural inconsistencies, notably for transgressing the constitutional principles of impartiality and the natural judge, being the genesis of procedural nullity. In this context, it is intended to answer the following problem: would the simplification of the procedure, involving the drafting of the awarded cooperation agreement, with the extinction of the double judicial analysis of the referenced agreement, contribute to enhancing the fight against corruption without affecting the fundamental guarantees of the accused? In response to the problem, we use the analysis of case law and legal theory on the subject, including a comparative study between similar foreign legal institutes.